2014
DOI: 10.3389/fphys.2014.00266
|View full text |Cite
|
Sign up to set email alerts
|

ABC transporters in fish species: a review

Abstract: ATP-binding cassette (ABC) proteins were first recognized for their role in multidrug resistance (MDR) in chemotherapeutic treatments, which is a major impediment for the successful treatment of many forms of malignant tumors in humans. These proteins, highly conserved throughout vertebrate species, were later related to cellular detoxification and accounted as responsible for protecting aquatic organisms from xenobiotic insults in the so-called multixenobiotic resistance mechanism (MXR). In recent years, rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 92 publications
3
44
0
Order By: Relevance
“…A less sensitivity of Abcb1 upon exposure to 2,3,7,8-TCDD as well as nano-TiO 2 has been observed in our study for single chemicals exposure while fish exposed to both showed a significant down regulation of Abcb1 gene expression. Our findings are in agreement with previous work done on fish species in which Abcb1 gene results less responsive and even more difficult to assess as reported for instance in sea bass by Ferreira et al (2014) while Abcc1-2 and Abcg2 are generally up-regulated by different xenobiotics.…”
Section: Phase 0 and III Biotransformation Gene Expressionsupporting
confidence: 94%
See 1 more Smart Citation
“…A less sensitivity of Abcb1 upon exposure to 2,3,7,8-TCDD as well as nano-TiO 2 has been observed in our study for single chemicals exposure while fish exposed to both showed a significant down regulation of Abcb1 gene expression. Our findings are in agreement with previous work done on fish species in which Abcb1 gene results less responsive and even more difficult to assess as reported for instance in sea bass by Ferreira et al (2014) while Abcc1-2 and Abcg2 are generally up-regulated by different xenobiotics.…”
Section: Phase 0 and III Biotransformation Gene Expressionsupporting
confidence: 94%
“…The similarities observed for Abcb1, Abcc1-1 and Abcg2 genes with other fish and mammals confirm the suitability of liver gene expression profile for ecotoxicological studies in order to increase the current knowledge on their role in organ defense from toxicant exposure (Ferreira et al, 2014;Luckenbach et al, 2014). According to the literature, contradictory results are present on ABC gene expression in liver of fish species upon exposure to aquatic toxicants including polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) including dioxin-like PCBs.…”
Section: Phase 0 and III Biotransformation Gene Expressionmentioning
confidence: 55%
“…Physiological acclimatization of fish to metals involves increased proliferation and hypertrophy of mucus-producing goblet cells; mucus chelates metals, reducing their availability [48]. MDR1, which pumps xenobiotics (such as toxins or drugs) back into the intestinal lumen, is a prime candidate for transport-related adaptation in fish [49]. The expression of this gene in F. heteroclitus from a contaminated site was shown to be two- to threefold higher than in fish from reference sites, but whether this resulted from adaptation is not known [50].…”
Section: Physiological Mechanisms For Adaptations and Their Potentialmentioning
confidence: 99%
“…protein plays a similar role to P-gp protein [23]. Importantly, the expression pattern of Abcb4 in zebrafish which is similar to ABCB1 gene, mainly distributed in brain and intestinal tissues [24].…”
Section: Discussionmentioning
confidence: 98%